2017
DOI: 10.1038/s41598-017-03217-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 and miR-145 disrupt the cervical epithelial barrier through dysregulation of cell adhesion, apoptosis and proliferation

Abstract: Molecular mechanisms regulating preterm birth (PTB)-associated cervical remodeling remain unclear. Prior work demonstrated an altered miRNA profile, with significant increases in miR-143 and miR-145, in cervical cells of women destined to have a PTB. The study objective was to determine the effect of miR-143 and miR-145 on the cervical epithelial barrier and to elucidate the mechanisms by which these miRNAs modify cervical epithelial cell function. Ectocervical and endocervical cells transfected with miR-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 49 publications
3
42
0
1
Order By: Relevance
“…The cervix has several critical functions including (1) maintenance of the integrity of the cervical epithelial barrier that lines the cervical lumen and acts to prevent microbial invasion and infection and (2) appropriate timing of cervical remodeling to prepare for delivery. Previous studies by our group and others have shown that many factors can promote a breakdown in the cervical epithelial barrier and initiate cervical remodeling through alterations in inflammation and infection ( Nold et al, 2012 ), microRNAs (miRNAs) ( Anton et al, 2017 ), biomechanical properties of the cervix ( Yoshida et al, 2016 ; Barnum et al, 2017 ), and the CV metabolome ( Ghartey et al, 2015 , 2017 ) and microbiome ( Romero et al, 2014a ; Stout et al, 2017 ). Differentially expressed miRNAs in the CV space are associated with PTB ( Elovitz et al, 2014 ), short gestation ( Sanders et al, 2015 ), and disruption of the cervical epithelial barrier ( Anton et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cervix has several critical functions including (1) maintenance of the integrity of the cervical epithelial barrier that lines the cervical lumen and acts to prevent microbial invasion and infection and (2) appropriate timing of cervical remodeling to prepare for delivery. Previous studies by our group and others have shown that many factors can promote a breakdown in the cervical epithelial barrier and initiate cervical remodeling through alterations in inflammation and infection ( Nold et al, 2012 ), microRNAs (miRNAs) ( Anton et al, 2017 ), biomechanical properties of the cervix ( Yoshida et al, 2016 ; Barnum et al, 2017 ), and the CV metabolome ( Ghartey et al, 2015 , 2017 ) and microbiome ( Romero et al, 2014a ; Stout et al, 2017 ). Differentially expressed miRNAs in the CV space are associated with PTB ( Elovitz et al, 2014 ), short gestation ( Sanders et al, 2015 ), and disruption of the cervical epithelial barrier ( Anton et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, proteins involved in cell-cell adhesion and cell motility can be targeted by both microRNAs. For example, the cell-cell adhesion protein JAM-A [102] and the actin bundling protein FSCN1 [55,72,[102][103][104][105] have both been described as miR-145 targets, suggesting inhibition of cell adhesion and movement. Indeed, overexpression of miR-145 in breast cancer cell lines decreased actin stress fibers, and miR-143 was shown to regulate ADDUCIN 3 [106] and FIBRONECTIN [21,49], leading to reduced cell migration.…”
Section: Proposed and Validated Targets Of The Micrornasmentioning
confidence: 99%
“…In cancer cells, Chen Z et al showed that miR-145 over-expression decreased the proliferation of prostate cancer cells and promoted cell apoptosis [32]. Anton L et al [33] also found that transfection of miR-145 could restrain cervical cell multiplication through increasing apoptosis and blocking cell cycle. In brief, these studies indicated that the over-expression of miR-145 expedited apoptosis in cells of various diseases, which may be a potential target for the treatment of some diseases.…”
Section: Down-regulated Mir-145 Rescued the Ir In Huvecsmentioning
confidence: 99%